Semi-Inverse Method in the Nonlinear Dynamics - Manevitch, Leonid I.; Smirnov, Valeri V. (NTU "KhPI", 2016)
The semi-inverse method based on using an internal small parameter of the nonlinear problems is discussed on the examples of the chain of coupled pendula and of the forced pendulum. The efficiency of such approach is highly appeared when the non-stationary dynamical problems are considered. In the framework of this method we demonstrate that both the spectrum of nonlinear normal modes and the interaction of them can be analysed successfully.
Keywords: nonlinear dynamics; semi-inverse method; nonlinear normal modes